2017
DOI: 10.1111/eva.12576
|View full text |Cite
|
Sign up to set email alerts
|

Inferring epidemiologic dynamics from viral evolution: 2014–2015 Eurasian/North American highly pathogenic avian influenza viruses exceed transmission threshold, R0 = 1, in wild birds and poultry in North America

Abstract: Highly pathogenic avian influenza virus (HPAIV) is a multihost pathogen with lineages that pose health risks for domestic birds, wild birds, and humans. One mechanism of intercontinental HPAIV spread is through wild bird reservoirs, and wild birds were the likely sources of a Eurasian (EA) lineage HPAIV into North America in 2014. The introduction resulted in several reassortment events with North American (NA) lineage low‐pathogenic avian influenza viruses and the reassortant EA/NA H5N2 went on to cause one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
5
19
0
Order By: Relevance
“…Additionally, other variables that represent potential migratory stopover habitats, such as Important Bird Areas and agricultural land, were not supported within the model, suggesting that if wild birds contributed to HPAI dispersal within the Midwest, their role was limited. This further supports previous studies, which indicated that the Midwestern portion of the outbreak was driven by inter-farm transmission (11,12,14). Several mechanisms have been proposed to explain HPAI transmission between farms during the 2015 outbreak, including equipment sharing, personnel overlap, and aerosolization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, other variables that represent potential migratory stopover habitats, such as Important Bird Areas and agricultural land, were not supported within the model, suggesting that if wild birds contributed to HPAI dispersal within the Midwest, their role was limited. This further supports previous studies, which indicated that the Midwestern portion of the outbreak was driven by inter-farm transmission (11,12,14). Several mechanisms have been proposed to explain HPAI transmission between farms during the 2015 outbreak, including equipment sharing, personnel overlap, and aerosolization.…”
Section: Discussionsupporting
confidence: 92%
“…Despite frequent reports of wild birds on the grounds and within barns of HPAI-positive turkey premises (10), a case-control study found no significant difference in exposure to wild birds between positive turkey premises and matched controls (11). Similarly, one phylodynamic analysis found no evidence of continued HPAI introductions into the Midwestern poultry industries (12), but other models have suggested multiple introductions (13,14). Geographic and environmental variables, such as human population, agricultural, climatological, and ecological measures, may help explain farm-to-farm transmission observed within the poultry industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America, genetic studies of puma (Puma concolor) and bobcat (Lynx rufus) populations indicate altered patterns of viral disease transmission and animal health in response to anthropogenic changes (Lee et al 2012;Ernest et al 2014;Carver et al 2016;Fountain-Jones et al 2017). Moreover, projects that integrate NGS tools can provide detailed information on the transmission of transcontinental diseases such as the spread of rabies in North America and in East Africa (Brunker et al 2015;Trewby et al 2017), and diseases circulating between wild and domesticated livestock on local and global scales (Nomikou et al 2015;Kamath et al 2016;Trewby et al 2016;Dippenaar et al 2017;Grear et al 2018).…”
Section: Integration With Genomicsmentioning
confidence: 99%
“…Complementing the work by Joseph et al., ; Grear, Hall, Dusek, and Ip () investigated mechanisms of intercontinental highly pathogenic avian influenza virus (HPAIV) spread through wild bird reservoirs possibly related to the North America outbreak in 2014. This introduction resulted in several reassortment events with North American (NA) lineage low‐pathogenic avian influenza viruses and the reassortant EA/NA H5N2 that went on to cause one of the largest HPAIV poultry outbreaks in North America.…”
Section: Themes Of the Special Issuementioning
confidence: 99%